Opto-acousto-fluidic microscopy for three-dimensional label-free detection of droplets and cells in microchannels. Issue 9 (5th April 2018) - Song, Chaolong; Jin, Tian; Yan, Ruopeng; Qi, Weizhi; Huang, Tianye; Ding, Huafeng; Tan, Say Hwa; Nguyen, Nam-Trung; Xi, Lei
Abstract : We present here a novel opto-acousto-fluidic microscopy approach for three-dimensional label-free detection of droplets and cells in microfluidic networks. Abstract : This paper reports a novel method, opto-acousto-fluidic microscopy, for label-free detection of droplets and cells in microfluidic networks. Leveraging the optoacoustic effect, the microscopic system possesses capabilities of visualizing flowing droplets, analyzing droplet contents, and detecting cell populations encapsulated in droplets via the sensing of acoustic waves induced by the intrinsic light-absorbance of matter.